Decolonising the Rainbow Flag - Laskar, Pia; Johansson, Anna; Mulinari, Diana (2017)
The aim of the article is to explore the location and the meaning given to the rainbow flag in places outside the hegemonic center. Through three case studies in the global North and South, held together by a multi-ethnographic approach, as well as a certain theoretical tension between the rainbow flag as a boundary object and/or a floating signifier, we seek to study where the flag belongs, to whom it belongs, with particular focus on how. The three case studies, which are situated in a city in the Global South (Buenos Aires), in a conflict war zone in the Middle East (the West Bank) and in a racialised neighbourhood in the Global North (Sweden), share despite their diversity a peripheral location to hegemonic forms of knowledge production regimes. Central to our analysis is how the rainbow flag is given a multitude of original and radical different meanings that may challenge the colonial/Eurocentric notions which up to a certain extent are embedded in the rainbow flag.